Investigating the protective effect of melatonin on liver injury related to myocardial ischemia-reperfusion - Colak, Cemil; Parlakpinar, Hakan; Ozer, Mehmet Kaya; Sahna, Engin; Cigremis, Yilmaz; Acet, Ahmet (Int Scientific Information, Inc, 2007)
Background: An animal model of myocardial ischemia-refusion (MI/R) was used to test the hypothesis that free radicals released with MI/R have hazardous effects out liver through remote organ injury. Material/Methods: Twenty-one rats were divided into three groups: sham-treated, MI/R, and MI/R+melatonin. To produce MI/R, a branch of the left coronary artery was occluded for 30 min followed by two hours of reperfusion. Melatonin or vehicle was given 10 min before ischemia. At the end of the study, liver tissue was obtained for biochemical determination. The false discovery rate (FDR) is explained and was used for multiple comparisons of the groups' means. Results: Compared with the sham group, MI/R significantly decreased glutathione (GSH) content and increased levels of nitric oxide (NO) and malondialdehyde (MDA). Melatonin administation significantly increased GSH levels and decreased the levels of NO and MDA compared with the MI/R group. Conclusions: Melatonin could prevent liver damage due to its strong antioxidant and free radical scavenger effects. Therefore, melatonin may have beneficial effects on remote organ injury such as MI/R-induced liver disorders.
Keywords: false discovery rate; liver injury; melatonin; myocardial ischemia-reperfusion; rat